Parental support in nurturing self-efficacy: understanding youth expectations during early adolescence - Nafiah, Rizka Khoirun; Izzaty, Rita Eka (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research investigates the impact of youth expectations and parental support on the self-efficacy of early adolescents in Madiun City, amid growing concerns about students’ struggles with self-confidence under academic pressures. Employing a quantitative approach, the study sampled 70 seventh-grade students from a broader demographic of over 8,000 across 14 junior high schools, a constraint imposed by the COVID-19 pandemic. Data were gathered through questionnaires and analyzed using multiple regression analysis. The findings underscore the profound effect of both adolescents’ expectations and parental support on their self-efficacy, highlighting these as significant predictors of students’ confidence in their ability to meet goals. This study’s implications are far-reaching, suggesting that educational and parental strategies focusing on enhancing positive expectations and robust support systems can play a critical role in improving self-efficacy among early adolescents. By addressing these factors, educators and parents can significantly contribute to bolstering students’ self-belief, potentially leading to improved academic outcomes and better psychological well-being.